COMMUNICATIVE-DISCURSIVE STRATEGIES OF CONSTRUCTING THE IMAGE OF CHINA IN THE UKRAINIAN INFORMATION SPACE - Qin, Song (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article examines communicative-discursive strategies for forming China’s image in the Ukrainian information space, which are based on genre-discursive and linguopragmatic approaches that allow systematizing genre-specific features of information presentation and identifying rhetorical techniques and communicative strategies characteristic of news agencies, analytical editions, economic and socio-political media, as well as social platforms, including Facebook, Telegram, YouTube, and Medium, which ensures the multidimensionality of media discourse research and contributes to identifying their influence on the formation of the country’s international image. The study employs methods of discourse analysis, content analysis, and comparative analysis, which enable distinguishing dominant rhetorical techniques and genre characteristics of information presentation that shape an ambivalent perception of China’s image in the Ukrainian information space, confirming the multifaceted nature of media positioning approaches for international actors.______________References:• Fairclough, N. (1995). Critical Discourse Analysis: The Critical Study of Language. London: Longman. https://www.felsemiotica.com/descargas/Fairclough-Norman-Critical-Discourse-Analysis.-The-Critical-Study-of-Language.pdf• van Dijk, T. A. (2008). Discourse and Power. London: Palgrave Macmillan.• Foucault, M. (1972). The Archaeology of Knowledge. London: Tavistock Publications. https://books.google.com.ua/books?id=kyKuUTYEn5sC&pg=PR3&hl=ru&source=gbs_selected_pages&cad=1#v=onepage&q&f=false• Perelman, Ch. (1982). The Realm of Rhetoric. Notre Dame: University of Notre Dame Press.• Nye, J. S. (2005). Soft Power: The Means to Success in World Politics. New York: Public Affairs. http://www.tinyurl.com/2b5wv9az• Fuchs, C. (2021). Social Media: A Critical Introduction (3rd ed.). London: Sage. https://fuchsc.net/wp-content/SocM_Preface_Intro.pdf• Ukrinform. (2021, April 22). Kytai vzyav zobov'iazannia do 2060 roku dosiahnyty nulovykh vykydiv CO₂. https://www.ukrinform.ua/rubric-world/3233118-kitaj-vzav-zobovazanna-do-2060-roku-dosagti-nulovih-vikidiv-co2.html (Accessed March 17, 2025).• RBK-Ukraine. (2021, April 18). SSHA i Kytai ob'iednaiut zusyllia, aby pereshkodity zminam klimatu. https://www.rbc.ua/ukr/news/ssha-kitay-obedinyat-usiliya-chtob-pomeshat-1618712290.html (Accessed March 17, 2025).• Dzerkalo tyzhnia. (2025, March 9). Kytai zrobyv vysnovky z pershoi torgovoi viiny z Trampom i zminyv taktyku na tli novykh taryfiv – AP. https://zn.ua/ukr/china/kitaj-zrobiv-visnovki-z-pershoji-torhovoji-vijni-z-trampom-i-zminiv-taktiku-na-tli-novikh-tarifiv-ap.html• Dzerkalo tyzhnia. (2025, January 31). Kytai planuie zakryty Panams'kyi kanal – Marko Rubio. https://zn.ua/ukr/usa/kitaj-planuje-zakriti-panamskij-kanal-marko-rubio.html• Yevropeiska pravda. (2021, March 26). Pekin vziavsia za sanktsii: yak daleko zayde konflikty Kitaiu ta YES. https://www.eurointegration.com.ua/articles/2021/03/26/7121377/• Yevropeiska pravda. (2021, July 14). Kytaiiski investytsii: dosvid Skhidnoi Yevropy dlia Ukrainy. Vidpovidaiemo na kliuchovi pytannia. https://www.eurointegration.com.ua/articles/ 2021/07/14/7125417/• Ekonomichna pravda. (2025, March 4). Kytaiiskyi vyrobnyk elektrovybiliv BYD zaluchae 5,6 miliarda dolariv dlia ekspansii za korodon. https://epravda.com.ua/biznes/kitayskiy-gigant-byd-zaluchaye-5-6-mlrd-dol-dlya-globalnoji-ekspansiji-#:~:text=Китайський%20виробник%20електромобілів%20BYD%20залучає,доларів%20для%20експансії%20за%20кордон&text=Китайський%20лідер%20з%20виробництва%20електромобілів,Про%20це%20пише%20Financial%20Times• (2024, February 12). Kytai naybil'sh zaatsiavlenyi u zavershennyi viiny v Ukraini: 5 faktiv, iaki tse pidtrymuiut'. https://minfin.com.ua/ua/2024/02/12/121377682/• Ekonomichna pravda. (2023, September 20). Masshtabni subsydiї Kytaiu u vyrobnytstvo elektrovybiliv potrebuiut' rozsliduvannia – YEK. https://epravda.com.ua/news/2023/09/20/704537/• Livy Berih. (2023, June 2). Viina v Ukraini ne zminyla pohliadiv Kytaiu shchodo mozhlyvoho napadu na Taivan', – Mizhnarodnii instytut stratehichnykh doslidzhen'. https://lb.ua/world/ 2023/06/02/558491_viyna_ukraini_zminila_poglyadiv.html• (2024, July 27). Zrozumity Kytai. Chy mozhe Pekin zupynyty viinu v Ukraini? (Chastyna 1). https://lb.ua/world/2024/07/27/626275_zrozumiti_kitay_chi_mozhe_pekin.html• Holos Ukrainy. (2022, February 9). Etnichna polityka Kytaiu: istoriia i suchasnist'. https://www.golos.com.ua/article/355972• Uryadovyi kur'ier. (2024, April 23). Kytai vidkydaiet' zvynuvachennia u pidtrymci rosiiskoho vtohrannia v Ukrainu. https://ukurier.gov.ua/uk/news/kitaj-vidkidaye-zvinuvachennya-u-pidtrimci-rosijsk/• (2024, March 12). https://www.facebook.com/• (2024, February 5). https://medium.com/• (2024, January 21). https://www.youtube.com/• (2024, March 14). https://www.instagram.com/
Keywords: China, communicative-discursive strategies, communicative tactics, Ukrainian media, media discourse, linguopragmatic approach, media representation, information space